Effect of low-dose rivaroxaban on bleeding events in low-weight patients with nonvalvular atrial fibrillation: a retrospective propensity score-matched cohort study - Liu, Yuan; Lai, Hengli; Chen, Zhenhuan; Xiong, Ganwei (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveTo investigate the effect of low-dose rivaroxaban on bleeding events in low-weight patients with nonvalvular atrial fibrillation.MethodsA retrospective study was conducted in patients with nonvalvular atrial fibrillation (weight ≤ 60 kg) who were admitted to the Department of Cardiology of Jiangxi Provincial People's Hospital from June 1, 2022, to December 12, 2022 and received anticoagulant therapy with rivaroxaban. The patients were divided into standard-dose group (15–20 mg) and low-dose group (10–15 mg). The patients were followed up for an average of 15 months by outpatient examination, telephone follow-up, or medical record inquiry of readmission patients. The bleeding events of the two groups were recorded during the follow-up period, and the two groups were balanced by propensity score weighting.ResultsA total of 198 patients with NVAF and body weight ≤60 kg receiving rivaroxaban anticoagulation therapy were enrolled, including 65 patients in the standard-dose group (15–20 mg) and 133 patients in the low-dose group (10–15 mg). In this study, only 24.1% (65/241) of the patients followed the standard dose of rivaroxaban. There was no significant difference in the incidence of bleeding events between the two groups after the balance of baseline characteristics (age) (P > 0.05). This was also consistent in patients weighing less than 50 kg.ConclusionsIn the real world, in lower-weight patients with nonvalvular atrial fibrillation, a reduced dose of rivaroxaban did not reduce the risk of bleeding, and this was consistent in patients weighing less than 50 kg.